Time-to-collision for the Pedestrian Protection System simulation - Roșu, Ioana-Alexandra; Carabulea, Laurențiu; Buzdugan, Ioana-Diana; Antonya, Csaba (Elsevier BV, 2023)
The development of autonomous vehicles has increased significantly, with a high focus on driving safety. Pedestrian avoidance systems are a top priority for ensuring higher pedestrian safety. The Pedestrian Protection System (PPS) is mainly observed in current research to analyze the impact of the time-to-collision for collision avoidance with a pedestrian for different vehicle speed variations. The PPS is a critical system that prevents vehicle and pedestrian collisions based on multiple sensors such as camera and RADAR (radio detection and ranging). Time-to-collision value represents a reliable parameter for the PPS for classifying the traffic conflict between a vehicle and a pedestrian as an inevitable or avoidable event. Simcenter Prescan was used to simulate the traffic infrastructure, the vehicle dynamics of the models, and the sensors. This study aims to evaluate the potential impact of different values of the time-to-collision parameter on the avoidance of collision with the pedestrian. The results showed that Pedestrian Protection System could completely avoid a pedestrian collision.
Keywords: autonomous vehicle; collision avoidance; Simcenter Prescan; critical scenario; time-to-collision